الحوسبة السحابية ومساهمتها في تحليل البيانات الضخمة في منظمات الاعمال - غوار, جمال; غربي, العيد (University of Eloued جامعة الوادي, 2022)
The increase in the amount of data available on the Internet and its rapid and massive spread have led to high storage costs for business organizations today, Consequently, many organizations tended to make their applications available for use through the Internet in what is known today as cloud computing. This study aims to demonstrate the importance of using cloud computing for business organizations today in analyzing big data in light of the world's trend towards a digital economy based on modern technology. The study also dealt with the concept of cloud computing, its characteristics and the most important models, In addition to addressing the concept of big data and its fields of application such as improving education, medical and military fields, decision-making process and improving services and products, Among the most prominent results reached is that business organizations today have to enter the world of cloud computing an urgent necessity imposed by the requirements of the current stage, and the rapid technological progress witnessed by the world.
Cloud computing and its contribution to big data analysis in business organizations
مداخلة. الملتقى الدولي الافتراضي حول: البيانات الضخمة والاقتصاد الرقمي كآلية لتحقيق الإقلاع الاقتصادي في الدول النامية "الفرص، التحديات والآفاق"
Keywords: الحوسبة السحابية، البيانات الضخمة، تحليل البيانات الضخمة; Cloud Computing; big data; Big data analysis.